Service Quality On User Satisfaction With The MyTelkomsel E-Service Mobile Application - Ananda Utami; Muhamad Alda; Fatimah Azzahra Putri; Bazlina Dini Amanda (UNIVERSITAS STEKOM, 2025)
This study aims to gain an in-depth understanding of the influence of user experience and e-service quality on user satisfaction with the MyTelkomsel mobile application. This research was conducted using a descriptive qualitative method along with data collection techniques in the form of semi-structured interviews and direct observation of active users of the MyTelkomsel application in the city of Medan. Data was obtained from 10 informants selected using purposive sampling techniques, supported by documentation of user interactions with the application. The results of the study indicate that ease of navigation, informative interface display, application response speed, and service feature reliability are the main factors that shape user satisfaction. Users tend to feel satisfied when the application is able to provide a comfortable, efficient, and responsive user experience that meets their needs. The findings of this study are expected to provide strategic input for Telkomsel in improving user experience and service quality as an effort to strengthen customer satisfaction and loyalty.